Assessing the effectiveness of policy interventions to reduce the use of agency or temporary social workers in England. (24th January 2013) - Cornes, Michelle; Manthorpe, Jill; Moriarty, Jo; Blendi‐Mahota, Saidah; Hussein, Shereen
Abstract There has been growing concern that English local authorities are over reliant on temporary staff to meet the shortage of social workers. This has been criticised as inefficient and costly while leading to problems of continuity and consistency for people using social work services. Focussing on recent policy and the implementation of new administrative procedures for the procurement and management of temporary or agency staff, this article explores progress being made towards achieving the previous government's policy goal that by 2020 local authorities will no longer need to rely on agency workers to carry out tasks that would normally be carried out by a permanent social worker. The article draws on the findings of an exploratory study (2007–2010) commissioned by the Department of Health which comprised of the following: a survey of local councils in England with adult social services responsibilities; case studies in three different localities; and qualitative interviews with stakeholders (n = 93). The findings suggest that while local authorities have reduced the costs of employing temporary staff through the setting up of intermediary control mechanisms, agency social workers continue to play important roles in teams and services.